Wildlife in Urban Landscapes: Use of Golf Course Ponds by Wetlands Birds - C. LeAnn White; Martin B. Main (EDIS)
This document describes the numbers and types of wetland-dependent birds, collectively referred to as “waterbirds,” recorded using golf course ponds during a study of 183 ponds on 12 golf courses over a 2-year period in Southwest Florida. We also provide recommendations based on this study that can be implemented to improve habitat on golf course and stormwater retention ponds for waterbirds. This document is WEC 188, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. Publication date: December 2004.